A boosting ensemble learning based hybrid light gradient boosting machine and extreme gradient boosting model for predicting house prices. Issue 4 (22nd November 2022) - Sibindi, Racheal; Mwangi, Ronald Waweru; Waititu, Anthony Gichuhi
Abstract: The implementation of tree‐ensemble models has become increasingly essential in solving classification and prediction problems. Boosting ensemble techniques have been widely used as individual machine learning algorithms in predicting house prices. One of the techniques is LGBM algorithm that employs leaf wise growth strategy, reduces loss and improves accuracy during training which results in overfitting. However, XGBoost algorithm uses level wise growth strategy which takes time to compute resulting in higher computation time. Nevertheless, XGBoost has a regularization parameter, implements column sampling and weight reduction on new trees which combats overfitting. This study focuses on developing a hybrid LGBM and XGBoost model in order to prevent overfitting through minimizing variance whilst improving accuracy. Bayesian hyperparameter optimization technique is implemented on the base learners in order to find the best combination of hyperparameters. This resulted in reduced variance (overfitting) in the hybrid model since the regularization parameter values were optimized. The hybrid model is compared to LGBM, XGBoost, Adaboost and GBM algorithms to evaluate its performance in giving accurate house price predictions using MSE, MAE and MAPE evaluation metrics. The hybrid LGBM and XGBoost model outperformed the other models with MSE, MAE and MAPE of 0.193, 0.285, and 0.156 respectively. Abstract : The article proposes an integration of advanced ML algorithms, LGBM and XGBoost techniques in predicting house prices. The proposed model is compared to individual boosting ensemble learning algorithms to evaluate its performance. The hybrid LGBM and XGBoost model has better performance accuracy results in predicting house prices compared to the individual models.